Jawabanmu

2014-05-01T00:09:10+07:00
Lim √(x -2) - √(10 - 4) = lim (√(x -2) - √(10 - x))(√(x -2) + √(10 - x))(6 +√(5x+6))
x⇒6      6 - √(5x+6)      x⇒6    ( 6 - √(5x+6))(√(x -2) + √(10 - x))(6 + √(5x+6))
                                   lim           (x-2-10+x)(6 +√(5x+6)
                                   x⇒6 (36-5x-6)(√(x -2) + √(10 - x))
                               = lim 2(x -6)(6 + √(5x + 6))
                                  x⇒6 -5(x-6)(√(x -2) + √(10 - x))
                               = lim 2(6 + √(5x + 6))
                                  x⇒6 -5(√(x -2) + √(10 - x))
                               = 2(6 + 6)
                                 -5(2 + 2)
                               = 24/-20
                               = - 6/5